Efektivitas Pelaksanaan Program Pengembangan Usaha Ekonomi Kreatif Perempuan Dalam Upaya Meningkatkan Kesejahteraaan Keluarga Pada Dinas Pemberdayaan Perempuan,Perlindungan Anak Pengendalian Penduduk Dan Keluarga Berencana Provinsi Sulawesi Tenggara - Erlangga, Teguh; Gunawan, Gunawan; Darpin, Darpin (REZ PUBLICA, 2020)
This study aims to determine and describe the effectiveness of the implementation of women's creative economic business development programs and describe the contribution of women's creative economic business development programs in an effort to improve the family welfare of women economic entrepreneurs fostered by the Office of Women's Empowerment, Child Protection, Population Control and Family Planning in Southeast Sulawesi Province with the research method used is descriptive qualitative, is a description of the results of observations, interviews and documentation studies, the data that has been obtained will be analyzed qualitatively and described in descriptive form, The results showed that the implementation of the women's creative economy business development program at the Office of Women's Empowerment, Child Protection of Population Control and Family Planning of Southeast Sulawesi Province was quite effective, the dimensions of capital assistance for program implementation had been carried out quite well, the dimensions of assistance in the construction of infrastructure facilities had not been well organized , the dimensions of program assistance have been implemented quite well, then the dimension of institutional strengthening of the program has been implemented quite well, and from the dimension of strengthening program partnerships it has been implemented quite well, the existence of the program has contributed positively in supporting aspects of family welfare for good business people in the form of additional income to meet daily needs both in the form of an increase in basic needs and can meet expenses - expenses other than basic matters such as health costs and also costs family education.